Post-Fire Changes in Soil Chemistry of the Savannas of the Paraguayan Humid Chaco - Candia-Díaz, Ana Beatriz; Watler-Reyes, William Jefferson; Rasche-Álvarez, Jimmy Walter; Laino-Guanes, Rafaela; Rejalaga-Noguera, Larissa Karina (REVISTA TERRA LATINOAMERICANA, 2025)
Contradictory results regarding the ef fects of fire on the chemical properties of soil are found in the existing literature. This study evaluated the ef fects of burning on the pH, organic matter (OM), phosphorous (P), calcium (Ca), magnesium (Mg) and potassium (K) in the soil of savannas in the Benjamín Aceval district of the Paraguayan Humic Chaco, over the medium term (two years af ter the wildfire event). The selection of sampling sites was based on the Fire Severity Index (dNBR). The treatment factors were the type of land cover (savanna and flooded savanna), burn condition (burned and unburned), and sample depth (0-3 and 3-6 cm). Regarding pH, no significance was found with any factor or their interactions. For OM, a significant interaction was found between burn condition and sampling depth. For P, the interaction between the type of cover and depth was significant. Concerning C, M, and K, a significant ef fect was observed based on sampling depth. Overall, the results indicate that two years af ter the fire, the ef fects of burning on the chemical properties of the soil were limited and dependent on the evaluated variable.